Peranan Home Industry Keripik Sayur Dalam Upaya Meningkatkan Kesejahteraan Keluarga - Syarifiyanti , Nurum; Suryati , Suryati; Isnaini , Mohd Aji (CV. ITTC INDONESIA, 2023)
Vegetable chips is one of the household industries in Pangkul Jawa Village which is still very traditional with its processing tools and strategies used and how to promote its products by entrusting products to souvenir centers and restaurants. The method used in this research is qualitative method. The types of data used are primary data and secondary data. Data collection techniques in this study were carried out through observation, interviews, and documentation. The purpose of making a thesis entitled